Hubungan Fungsi Pengawasan dan Pengarahan Perawat Manajer dengan Penerapan Keselamatan Pasien - Suhesti, Tri; Nasution, Siti Zahara; Lubis, Zulhaida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the relationship between the supervisory and directing functions of nurse managers with the implementation of patient safety at the Special UPTD at the Prof. Mental Hospital. Dr. Muhammad Ildrem. The design of this research is cross-sectional which is included in the type of quantitative observational research. Determining the number of samples used the Slovin formula and the number of samples was 108 people. Sampling used proportional sampling technique. The data collection process uses an instrument in the form of a questionnaire. Analysis uses Chi-Square statistical correlation. Based on the research results, it was found that the supervision and direction functions had been carried out well by the nurse manager. The implementation of patient safety has been carried out by the nurses well and there is a relationship between the supervision and direction function with the implementation of patient safety at the UPTD Special for Prof. Mental Hospital. Dr. Muhammad Idrem. In conclusion, there is a relationship between the supervisory and directing functions carried out by the nurse manager on the good implementation of patient safety by nurses at the Special UPTD at the Prof. Mental Hospital. Dr. Muhammad Idrem. Keywords: Patient Safety, Supervision and Direction, Nurse Manager.